Do Epidural Catheter Size and Flow Rate Affect Bolus Injection Pressure in Different Programmed Intermittent Epidural Bolus Regimens? An In Vitro Study. Issue 2 (June 2020) - Krawczyk, P.; Piwowar, P.; Sałapa, K.; Lonc, T.; Andres, J.
Abstract : ( Anesth Analg . 2019;129:1587–1594) Epidural analgesia is the most effective technique for labor analgesia, and programmed intermittent epidural bolus (PIEB) is a modality for delivering epidural analgesia that is becoming increasingly popular. However, the optimal settings for the PIEB technique have not been established. This study was undertaken to examine combinations of catheter types and pump characteristics and how they might influence epidural bolus injection pressure and the triggering of pump alarms. The investigators hypothesized that higher gauge catheters plus increased flow rates would increase the bolus injection pressure.